2017
DOI: 10.1111/add.13860
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prescription drug monitoring programs (PDMPs) on opioid utilization among Medicare beneficiaries in 10 US States

Abstract: Prescription drug monitoring programs (PDMPs) are associated with reductions in opioid use, measured by volume, among disabled and older adult Medicare beneficiaries in the United States compared with states that do not have PDMPs. PDMP impact on daily doses and daily prescriptions varied by reason for eligibility and plan type. These findings cannot be generalized beyond the 10 US states studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 53 publications
2
82
1
Order By: Relevance
“…Using Medicare data, Meara et al (2016) finds no effect of the average state-level reform during the 2006-2012 period; suggestive evidence showing reductions in sales do not survive corrections for multiple hypothesis testing. These results contrast with Moyo et al (2017), which finds significant reductions in the total volume of opioids dispensed to Medicare patients following implementation of PDMPs. These studies of aggregate outcomes may be misleading if there are changes in the composition of patients or prescribed drugs.…”
Section: The Prescription Drug Epidemic and Policy Responsescontrasting
confidence: 74%
See 1 more Smart Citation
“…Using Medicare data, Meara et al (2016) finds no effect of the average state-level reform during the 2006-2012 period; suggestive evidence showing reductions in sales do not survive corrections for multiple hypothesis testing. These results contrast with Moyo et al (2017), which finds significant reductions in the total volume of opioids dispensed to Medicare patients following implementation of PDMPs. These studies of aggregate outcomes may be misleading if there are changes in the composition of patients or prescribed drugs.…”
Section: The Prescription Drug Epidemic and Policy Responsescontrasting
confidence: 74%
“…One of the largest and most comprehensive studies of prescribing behavior, Buchmueller and Carey (2018), uses Medicare Part D data from 2007-2012 to examine patients' prescription histories. This paper finds that PDMPs have the intended effect on supply, reducing the percentage of enrollees who obtain prescriptions from five or more physicians by more than 8 percent and from five or more pharmacies by more than 15 percent, with no effect on 13 For evidence on Schedule II prescriptions, see Bao et al (2016), Moyo et al (2017), and Wen et al (2017). 7 the mean of the utilization distribution.…”
Section: The Prescription Drug Epidemic and Policy Responsesmentioning
confidence: 88%
“…In two papers published recently in Addiction, Moyo et al [1] and Pardo [2] provide important contributions to the still nascent field of high-quality Prescription Drug Monitoring Program (PDMP) research. Broadly in line with similar analyses, Moyo et al report that PDMPs in some US states are associated with some changes in prescribing behavior, and Pardo that some PDMPs are protective of opioid analgesic (OA)-related death.…”
mentioning
confidence: 99%
“…In an analysis of Medicare beneficiaries in 10 states, Moyo et al [1] found PDMPs to be associated with a reduction in the volume of OAs prescribed, but not with changes in either the number of OA prescriptions issued or the mean morphine milligram equivalent (MME) per prescription. Consistent with previous research, changes were found to vary dramatically between states and subgroups, and were limited largely to Schedule II opioids [3][4][5][6].…”
mentioning
confidence: 99%
“…5,6,7,8,9,10,11 One premise of these supply-side interventions is that they will decrease the number of individuals exposed to opioid analgesics and subsequently prevent individuals from developing an opioid use disorder (OUD), ultimately lowering the number of opioid overdose deaths. Previous studies have shown that such interventions may lead to a modest decrease in the prescription opioid supply, especially programs with enrollment and/or use mandates.…”
Section: Introductionmentioning
confidence: 99%